(untitled) (Modern education and development, 2025)
In the world of medicine, knowledge of English is becoming an integral part of professional growth. For medical students, communicative English is not only a means of communication, but also the key to effective acquisition of new knowledge, scientific research, and a successful career in the international medical environment. This article is devoted to the importance of learning communicative English for future doctors, as well as methods and approaches that can help medical students master the necessary skills.